Pengharapan Akan Kedatangan Kembali Yesus Kristus Menurut (Wahyu 22:12) - Iswan Garamba (International Forum of Researchers and Lecturers, 2024)
The Second Coming of Jesus Christ is one of the profound topics in Christian theology. This article aims to explore the concept of hope in the return of Jesus Christ within the context of Christian theology and beliefs. The introduction provides a conceptual foundation on the meaning and relevance of the hope for the return of Christ for Christian believers. The methods used include the analysis of biblical texts, theological literature review, and related conceptual review. The results depict various theological perspectives on the Second Coming of Christ and its implications in everyday Christian life. A thorough discussion of eschatological theology and the perceptions of Christians regarding the return of Christ is the main focus of this article. The conclusion affirms the importance of understanding and responding to the hope for the return of Jesus Christ in spiritual life and Christian practice. This article contributes to a deeper understanding of essential aspects of the Christian faith and invites reflection on the significant meaning of hope for the return of Christ in a contemporary context. The bibliography presents key references supporting this research and theological analysis.